2011
DOI: 10.1016/j.jep.2011.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective activity of Zanthoxylum rhoifolium Lam. in animal models

Abstract: Our results indicate that the ethanolic extract of Zanthoxylum rhoifolium exhibits a significant gastroprotection, because it inhibits the formation of gastric lesions using different models. The release of the nitric oxide, the opening of the K(ATP) channels, the participation of the non-protein sulfhydril groups (NP-SH), catalase and the increase of mucous secretion seem to be involved in the gastroprotection activity of the EEZR. Nevertheless, this activity does not seem to be related to antisecretory mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
1
22
0
2
Order By: Relevance
“…This plant has been reported to have antimalarial, antinociceptive, antitumoral, and gastroprotective effects. The essential oil of its leaves and alkaloids isolated from the stem bark have antibacterial activity against gram-positive and -negative bacteria and antifungal activity against Aspergillus flavus, but no activity against Candida species was found (Gonzaga et al, 2003;Jullian et al, 2006;Silva et al, 2007;Boehme et al, 2008;Peneluc et al, 2009;Pereira et al, 2010;Freitas et al, 2011). Activity against Candida spp.…”
Section: Resultsmentioning
confidence: 99%
“…This plant has been reported to have antimalarial, antinociceptive, antitumoral, and gastroprotective effects. The essential oil of its leaves and alkaloids isolated from the stem bark have antibacterial activity against gram-positive and -negative bacteria and antifungal activity against Aspergillus flavus, but no activity against Candida species was found (Gonzaga et al, 2003;Jullian et al, 2006;Silva et al, 2007;Boehme et al, 2008;Peneluc et al, 2009;Pereira et al, 2010;Freitas et al, 2011). Activity against Candida spp.…”
Section: Resultsmentioning
confidence: 99%
“…The homogenates were then used for determining the enzymatic activities. All assays were carried out at the room temperature in triplicates [25].…”
Section: Measurement Of Gastric Enzyme Activitymentioning
confidence: 99%
“…Results of the study revealed that plant extract prevented the reduction in non-protein sulfhydril groups along with significant increase in mucus production and catalase levels. Phytochemical screening showed the presence of alkaloids, flavonoids and triterpenes in the ethanolic stem bark extract of Z. rhoifolium which might participate in gastroprotective activity of plant (Freitas et al, 2011).…”
Section: Zanthoxylum Rhoifoliummentioning
confidence: 99%